Implementing Transparency and Participation: An Overview in Public Service - Syam, Sitti Mutmainnah; Bachri, Syamsul; Moenta, Andi Pangerang (International Journal Papier Public Review, 2021)
This research aims to know and explain the application of the principles of good governance, namely the principles of transparency and participation and the constraints of applying the principles of transparency and participation in public services. The research method used is empirical research method, to achieve this goal, so this research uses data collection techniques through interviews, observations, document studies, and documentation. While the data sources used are primary and secondary data sources. The approach of this research is conceptual approach that is moving from the views or doctrines that develop in the science of law and the approach of the Law, namely the approach carried out by edilah regulation related to legal issues that are being studied. The results revealed that the principle of transparency has not run optimally because the SOP has not been informed to the public, the principle of participation has not run optimally because the management of complaints has not been good. Therefore, in the context of public services that are a very strategic part in measuring good governance needs to be optimized by providing SOP information on information boards, websites, brochures, opening complaints through social media or working with village officials, head of Cluster Area to directly socialize public service procedures and policies to the community.